The effect of muscle glycogen status on control of substrate metabolism during exercise - Weltan, Sandra Mary (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Glycogen depletion has frequently been shown to result in a decrease in respiratory exchange ratio (RER). However, the metabolic response to glycogen depletion has generally been studied in overnight fasted subjects or in subjects who were already fatigued, or hypoglycaemic, or both, raising the question of whether the differences seen were due to general "carbohydrate deficiency" or due specifically to muscle or liver glycogen depletion. If euglycaemia and especially hyperglycaemia is maintained, the " carbohydrate deficiency" is overcome. In addition, because insulin stimulates muscle glucose uptake and not liver glucose uptake during euglycaemia (except at very high concentrations), insulin infusion would differentiate between liver and muscle glycogen depletion, since if the decrease in RER previously observed is abolished with insulin infusion while euglycaemia is maintained, this would indicate that the decrease is specifically due to muscle glycogen depletion. Thus, the aim of this study was to investigate the metabolic effect of glycogen content while an adequate amount or an excess of carbohydrate was provided in the form of an intravenous glucose infusion and when plasma insulin concentrations are raised.